Fertility education for adolescent cancer patients: Gaps in current clinical practice in Europe. (21st June 2020) - Korte, Elisabeth; Schilling, Ralph; Balcerek, Magdalena; Campbell, Helen; Dirksen, Uta; Herrmann, Gloria; Kepakova, Katerina; Kepak, Tomas; Klco‐Brosius, Stephanie; Kruseova, Jarmila; Kunstreich, Marina; Lackner, Herwig; et al.
Abstract: Objective: As adolescent cancer patients may suffer from infertility following treatment, fertility counselling is essential. Our aim was to explore the current situation in four European countries in terms of (I) education about the risk for infertility, (II) counselling on fertility preservation, (III) patients' knowledge on fertility, (IV) sufficiency of information and (V) uptake of cryopreservation. Methods: In total, 113 patients (13–20 years) at 11 study centres completed a self‐report questionnaire three and six months after cancer diagnosis. Multivariate logistic regression was used to estimate odds ratios (OR) with 95% confidence intervals (CI). Results: As many as 80.2% of participants reported having received education about the risk for infertility prior to treatment, 73.2% recalled counselling on fertility preservation. Only 52.3% stated they felt sufficiently informed to make a decision. Inability to recall counselling on fertility preservation (OR = 0.03, CI: 0.00–0.47) and female gender (OR = 0.11, CI: 0.03–0.48) was associated with lower use of cryopreservation, whereas older age was associated with higher use. Conclusion: Fertility counselling was available to a relatively high proportion of patients, and it did influence the utilisation of cryopreservation. However, many patients did not feel sufficiently informed. Further improvement is needed to enable adolescent cancer patients to make an informed decision on fertility preservation.